The Antibacterial Activity of Infusion of Averrhoa bilimbi L Fruits and Cananga odorata Flowers against Frequently Pathogenic Bacteria - Lia Yulia Budiarti; Erida Wydiamala; Najiya Ulfa (Journal of Agromedicine and Medical Sciences, 2022)
Infectious diseases due to opportunistic bacteria and pathogens are still a health problem. Transmission can be prevented by using an alcohol-based antiseptic liquid or naturally. Averrhoa bilimbi L. fruit plants and Cananga odorata flowers contain bioactive compounds that can inhibit bacterial growth. This study aimed to analyze the infusion activity of Averrhoa bilimbi fruit and Cananga odorata flower in single and combined dosage forms against several frequently pathogenic bacteria in vitro. This posttest-only experimental study with a control group design used the paper disc diffusion method. Observation parameters were the diameter of the inhibition zone on the test bacteria after infusion treatment of 50%, 75%, and 100% A.bilimbi fruit and 100% C.odora flowers, as well as 70% alcohol. The results showed that the diameter of the inhibition zone in the combination treatment of A.bilimbi and C.odorata infusion was significantly different from that of the single preparation (p<0.05). The combination of 100% A.bilimbi and 100% C.odorata (ratio 1:1) produced the greatest effect and was equivalent to 70% alcohol. The average inhibition of the combination infusion of Staphylococcus aureus (17.36mm) and Staphylococcus epidermidis (17.57mm) was greater than that of Escherichia coli (14.48 mm) and Salmonella enterica serovar Typhi (14.12mm). In conclusion, the infusion of Averrhoa bilimbi fruit and the Cananga odorata flower had antibacterial activity, and the combined preparation produced a better inhibitory effect than the single preparation. Keywords: antibacterial activity, Averrhoa bilimbi L., Cananga odorata, infusion, single preparation, combination preparation